Stanisława Ligonia „Wesele na Górnym Śląsku” (PDF 2,53 MB) (Książnica Śląska, 2025)
The article is devoted to Stanisław Ligoń’s show Wesele na GórnymŚląsku (The Wedding in Upper Silesia). The premiere of the playtook place on January 22, 1930 at the Polish Theatre in Katowice.The author discusses the genesis of the play in detail, setting it ina broad context and reaching back to the beginnings of the popularity of “wedding” as a theme for theatrical works. He points out that in the Ligoń’s play the theme of “wedding” had an additional symbolic dimension – it illustrated the connection of Upper Silesia with thereborn Republic of Poland. The article also describes the play’s premiere and the stage history of the work from the interwar period tothe present day.